Photodynamic inactivation of Gram-positive bacteria employing natural resources - Mamone, Leandro Ariel (2014)
The aim of this paper was to investigate a collection of plant extracts from Argentina as a source of new natural photosensitizers (PS) to be used in Photodynamic Inactivation (PDI) of bacteria. A collection of plants were screened for phototoxicity upon the Gram-positive species Staphylococcus epidermidis. Three extracts turned out to be photoactive: Solanum verbascifolium flower, Tecoma stans flower and Cissus verticillata root. Upon exposure to a light dose of 55 J/cm2, they induced 4, 2 and 3 logs decrease in bacterial survival, respectively. Photochemical characterisation of S. verbascifolium extract was carried out. PDI reaction was dependent mainly on singlet oxygen and to a lesser extent, on hydroxyl radicals, through type II and I reactions. Photodegradation experiments revealed that the active principle of the extract was not particularly photolabile. It is noticeable that S. verbascifolium -PDI was more efficient under sunlight as compared to artificial light (total eradication vs. 4 logs decrease upon 120 min of sunlight). The balance between oxidant and antioxidant compounds is likely to be masking or unmasking potential PS of plant extracts, but employing the crude extract, the level of photoactivity of S. verbascifolium is similar to some artificial PS upon exposure to sunlight, demonstrating that natural resources can be employed in PDI of bacteria. © 2014 Elsevier B.V. All rights reserved.